Il Geoportale del Comune di Magliano in Toscana il webGIS e la generazione automatica dei CDU (GEOmedia, 2013)
In recent years, web GIS on urban issues has played a key role in modernizing many Italian Public Authorities. In line with these important technological changes, the municipality of Magliano in Toscana (GR ) has developed a mapping platform (Geoportal) providing important services for citizens. The main application of Geoportal is the WebGIS interface which allows people to consult and search government resources (the Urban Structure Plan) and maps (Regional Technical Cartography and Cadastre) online. Linked to this geographical interface, an application has been developed that allows authorized users to create Town Planning Certificates (CDU ) automatically. Through simple web screens with guided forms, users can print off a highly accurate document quickly, thereby improving the efficiency of council offices by reducing processing times.